Blockade of CC Chemokine Receptor Type 3 Diminishes Pain and Enhances Opioid Analgesic Potency in a Model of Neuropathic Pain - Pawlik, Katarzyna; Ciechanowska, Agata; Ciapała, Katarzyna; Rojewska, Ewelina; Makuch, Wioletta; Mika, Joanna (Frontiers in Immunology, 2021)
Neuropathic pain is a serious clinical issue, and its treatment remains a challenge in contemporary medicine. Thus, dynamic development in the area of animal and clinical studies has been observed. The mechanisms of neuropathic pain are still not fully understood; therefore, studies investigating these mechanisms are extremely important. However, much evidence indicates that changes in the activation and infiltration of immune cells cause the release of pronociceptive cytokines and contribute to neuropathic pain development and maintenance. Moreover, these changes are associated with low efficacy of opioids used to treat neuropathy. To date, the role of CC chemokine receptor type 3 (CCR3) in nociception has not been studied. Similarly, little is known about its endogenous ligands (C-C motif ligand; CCL), namely, CCL5, CCL7, CCL11, CCL24, CCL26, and CCL28. Our research showed that the development of hypersensitivity in rats following chronic constriction injury (CCI) of the sciatic nerve is associated with upregulation of CCL7 and CCL11 in the spinal cord and dorsal root ganglia (DRG). Moreover, our results provide the first evidence that single and repeated intrathecal administration of the CCR3 antagonist SB328437 diminishes mechanical and thermal hypersensitivity. Additionally, repeated administration enhances the analgesic properties of morphine and buprenorphine following nerve injury. Simultaneously, the injection of SB328437 reduces the protein levels of some pronociceptive cytokines, such as IL-6, CCL7, and CCL11, in parallel with a reduction in the activation and influx of GFAP-, CD4- and MPO-positive cells in the spinal cord and/or DRG. Moreover, we have shown for the first time that an inhibitor of myeloperoxidase-4-aminobenzoic hydrazide may relieve pain and simultaneously enhance morphine and buprenorphine efficacy. The obtained results indicate the important role of CCR3 and its modulation in neuropathic pain treatment and suggest that it represents an interesting target for future investigations.